Pengaruh Gender dalam Memoderasi Gaya Kepemimpinan terhadap Kinerja - Indra Rustiawan Rusman (Universitas La Tansa Mashiro, 2014)
The purpose of this study was to gain a proper understanding of the influence of leadership style on performance with gender as a moderating variable. This research is a field. This method is intended to test the influence of leadership style variable (X1) as the independent variable on the performance variable (Y) as the dependent variable, and examine the effect of gender (X2) as a moderating variable between leadership style and performance. Than 80 questionnaires administered, 75 (100%) is returned in full. The study found that gender moderates the influence of leadership style on performance.